1986
DOI: 10.1002/chin.198643150
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Indole‐Phenol Bioisosterism. Synthesis and Antihypertensive Activity of a Pyrrolo Analogue of Labetalol.

Abstract: Das Pyrrolo‐Analogon (XIa) des Labetalols (XII) wird ausgehend vom N‐Acetylindolin (I) entsprechend dem Formelschema in einer vielstufigen Reaktionssequenz hergestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Examination of the antihypertensive activity of the pyrrolo analogue 71 of labetalol (70, Figure 64), an R-and β-adrenergic receptor antagonist [127][128] provides further evidence for the successful use of the indole phenol bioisosteric replacements. 129 The indolo analogue 71 of labetalol (70) was found to reduce blood pressure in spontaneously hypertensive rats, without causing a decrease in heart rate. The antihypertensive activity of these compounds is related to their ability to hydrogen bond to the adrenergic receptors.…”
Section: Hydroxyl Group Bioisosteresmentioning
confidence: 99%
“…Examination of the antihypertensive activity of the pyrrolo analogue 71 of labetalol (70, Figure 64), an R-and β-adrenergic receptor antagonist [127][128] provides further evidence for the successful use of the indole phenol bioisosteric replacements. 129 The indolo analogue 71 of labetalol (70) was found to reduce blood pressure in spontaneously hypertensive rats, without causing a decrease in heart rate. The antihypertensive activity of these compounds is related to their ability to hydrogen bond to the adrenergic receptors.…”
Section: Hydroxyl Group Bioisosteresmentioning
confidence: 99%
“…Thus, the free phenol, which is critical for proton ionophore activity, may hinder the accumulation of our closantel-based compounds. Therefore, from this study, three possibilities for enhancing nematode penetrability are taking a prodrug approach by masking the free phenol, the synthesis of other analogues incorporating the functional groups identified in this report, and the synthesis of phenol isosteric scaffolds (e.g., indazole). …”
Section: Discussionmentioning
confidence: 99%
“…This approach has been useful for determining the nature of the hydrogen bonding between phenol-containing ligands and receptor proteins. [1][2][3][4] For example Asselin et al1 demonstrated that the "indolic" aminotetralin 2a (Figure 1) showed dopaminergic effects and thus mimicked the action of 7-hydroxy-2-(iV^V-dipropylamino)-l,2,3,4-tetrahydronaphthalene (7-OH-DPAT, lb). It was pointed out that, since the lone pairs in the indole nitrogen of 2a cannot participate in a H-bond (due to its contribution to the aromaticity), the indole NH moiety can only participate as a H-bond donor (electron-pair acceptor).…”
Section: Introductionmentioning
confidence: 99%